Effect of Hot Extrusion on the Microstructure and Mechanical Properties of the SiCp/Mg-9Al-1Zn Nanocomposite Fabricated by Different Stir Time. Issue 10 (October 2017) - Wanhua, Wang; Hongxia, Wang; Guangxiao, Ren; Weili, Cheng; Shaoxiong, Zhang
Abstract: 1wt% SiC nanoparticles reinforced Mg-9Al-1Zn magnesium matrix composite was fabricated by stir casting and hot extrusion. Effect of hot extrusion on microstructure and mechanical properties of SiCp/Mg-9Al-1Zn nanocomposite stirring for 10 min and 30 min was researched. The results show that the grains of the matrix in the as-cast SiCp/Mg-9Al-1Zn nanocomposite stirring for 30 min are mainly refined. But the mechanical properties of nanocomposite decline due to the increase of agglomerated SiC nanoparticles and Mg17 Al12 phases with network morphology along the grain boundaries. After hot extrusion, a bimodal microstructure composed of alternate arrays of fine DRXed grains and relatively coarse DRXed grains forms. Particularly, for extruded nanocomposites stirring for 30 min, the fine DRXed region increases and the distribution of SiC nanoparticles is more homogenous, which exhibits superior mechanical properties compared with as-extruded SiCp/Mg-9Al-1Zn nanocomposite stirring for 10 min.